2019
DOI: 10.16888/interd.2019.36.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad funcional e inclusión en Instituciones de Educación Superior (IES) en Medellín

Abstract: Psicóloga. Especialista en docencia investigativa universitaria, Magíster en intervenciones psicosociales. Docente investigadora en la Facultad AbstractThe main objective of this article is to present the reality evidenced in the field of higher education and the inclusive policies for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…De esta manera, se amplían las comprensiones conceptuales y los consecuentes esfuerzos por generar lineamientos y prácticas cotidianas en la escuela que, aunque empiezan a involucrar otras formas de diversidad, siguen anclados directamente con la discapacidad. Esto se corrobora con las investigaciones sobre inclusión y escuela, en donde prevalecen las acepciones a la discapacidad y a las dificultades de aprendizaje (Abrahão et al, 2020;Cuadrado, 2018;Mejía, 2019;Pagán et al, 2021), aportando pistas para comprender las implicaciones en el desarrollo de niños, niñas y adolescentes con relación al rendimiento académico, la deserción escolar, el acoso escolar, la discriminación y la inequidad en las oportunidades de aprendizaje.…”
Section: íNdice De Inclusión Educativa: Aportes De La Experienciaunclassified
“…De esta manera, se amplían las comprensiones conceptuales y los consecuentes esfuerzos por generar lineamientos y prácticas cotidianas en la escuela que, aunque empiezan a involucrar otras formas de diversidad, siguen anclados directamente con la discapacidad. Esto se corrobora con las investigaciones sobre inclusión y escuela, en donde prevalecen las acepciones a la discapacidad y a las dificultades de aprendizaje (Abrahão et al, 2020;Cuadrado, 2018;Mejía, 2019;Pagán et al, 2021), aportando pistas para comprender las implicaciones en el desarrollo de niños, niñas y adolescentes con relación al rendimiento académico, la deserción escolar, el acoso escolar, la discriminación y la inequidad en las oportunidades de aprendizaje.…”
Section: íNdice De Inclusión Educativa: Aportes De La Experienciaunclassified
“…(4) Likewise, the universal design for learning applies the concepts of accessibility and inclusion, beyond physical environments, designing teaching and learning opportunities in ways that are varied, accessible, and attractive for all students, even those with different needs, (5) therefore, it is proposed to create new forms of access to higher education for students with diversity, potentiate ongoing and initial teacher training programs, sensitize the university community, promote participation from students in said condition, establish inclusive public policies, improve accessibility, and disseminate basic information on themes of disability and inclusion. (6) With regards to the life project, it can change when acquiring a motor functional diversity due to the impact it generates on the parental, cultural, or social roles and assimilating a new environment and these influence directly on how to deal with adaptation; (7) furthermore, the environment might not have a physical infrastructure that facilitates their mobility in the study campus, as identified by a study that obtained that only one of nine universities in Medellín (Colombia) (8) had an environment adapted to the needs of students with physical diversity, and this is why a timely adaptation should be conducted of the student to the university campus.…”
Section: Introduction Imentioning
confidence: 99%
“…With regards to the life project, it can change when acquiring a motor functional diversity due to the impact it generates on the parental, cultural, or social roles and assimilating a new environment and these influence directly on how to deal with adaptation; 7 furthermore, the environment might not have a physical infrastructure that facilitates their mobility in the study campus, as identified by a study that obtained that only one of nine universities in Medellín (Colombia) 8 had an environment adapted to the needs of students with physical diversity, and this is why a timely adaptation should be conducted of the student to the university campus.…”
Section: Introductionmentioning
confidence: 99%
“…When discussing educational rights, conflicts in legal contexts are observed, not only in Brazil but also in other countries such as Portugal, Medellin in Colombia, where students with disabilities require quality and dignified education (Pereira & Albuquerque, 2017;Zapata, 2019). The issue of inclusive education for people with disabilities in public higher education is also a challenge in Uruguay (Gómez & Fernández, 2018).…”
Section: Introductionmentioning
confidence: 99%